Betting on the Stars: Fate and Faith in Girolamo Cardano’s Analysis of His Own Life - Liu, Yunfan (Transactions on Social Science, Education and Humanities Research, 2024)
Throughout the Renaissance, the major discussion on whether humans have free will is primarily incompatible with the belief in destiny. Girolamo Cardano, the Italian polymath and astrologer, has stalled into existential crises. Through his autobiography, The Book of My Life, Cardano’s faith in the predestined fate predicted by astrology and the desire for freedom and self-will collided, eventually leading to new ideas about the coexistence of human potential and the laws of nature. This research will examine how Cardano reconciles the tension between his deterministic belief in astrology-guided destiny and his faith in free will through The Book of My Life.